Effectiveness of Assessment Implementation in Civil Service Career Development at the Ministry of Home Affairs - Syahputra, Subhan; Soemartono, Triyuni; Nenobais, Harry (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama’ah, 2025)
Study purpose. This study aims to analyse the effectiveness of assessments in the career development of civil servants at the Ministry of Home Affairs. Assessments are used as instruments to measure the competence, potential, and performance of civil servants in order to support objective and merit-based career planning, including mapping employees for the purposes of transfers and promotions. Material and Methods. The research method used was a combination of qualitative and quantitative approaches through interviews, surveys, and documentation studies, with the Personnel Bureau as the assessment implementing unit and the locus of research. The theoretical basis used Gibson’s effectiveness theory, which covers seven aspects, namely productivity, quality, efficiency, flexibility, satisfaction, excellence, and development. Results. The study shows that structured and competency-based assessments can improve the accuracy of civil servant placement and promotion. However, obstacles are still found in implementation, including a limited number of assessors, resistance from civil servants, a lack of system support, and budget constraints. To overcome this, the Ministry of Home Affairs has taken a number of improvement measures, such as utilising digital technology and artificial intelligence (AI), increasing the number of certified assessors, ensuring transparency of results with clearer feedback, and integrating assessment data into an integrated HR management system. These efforts are expected to strengthen the effectiveness of assessments so that ASN career development becomes more objective, measurable, and sustainable. Conclusion. The implementation of assessments at the Ministry of Home Affairs has proven to be quite effective in supporting the career development of ASNs through the objective mapping of employee competencies and potential. Assessments improve the accuracy of job placements and promotions, although they are still constrained by limitations in assessors, budgets, ASN resistance, and system support. Improvement efforts through the use of digital technology and AI, an increase in certified assessors, transparency of results, and integration of assessment data are expected to strengthen the effectiveness of ASN career development to be more objective, measurable, and sustainable.